Heat treatment of carbohydrates to produce caramel color - Khalizatul Radhiah, Kasim (2010)

(untitled)
Caramel colors are brown powders or viscous liquids that are used to impart yellow to dark brown and have been used in carbonated beverages, distilled liquors, wines, pharmaceutical, extracts, bakery products, candy, soups, and baked beans for decades. This color additive can be prepared from various sources of carbohydrates such as glucose, corn, molasses, wheat, and tapioca hydrolysates by controlled heat treatment in the presence of certain reactants. The purpose of this study is to produce caramel color from different sources of carbohydrates as well as investigate the effect of pH on the development of the browning reactions. In this study, two set of experiments were conducted. The first is production of caramel color from glucose solution. Glucose sample of different pH are pre-heated in water bath at 100°C and further heated at caramelization temperature of 121°C in paraffin bath. The color development was monitored using U-1800 Hitachi UV-Visible Spectrophotometer. The second experiment is production of caramel color using starch hydrolysates produced from acid hydrolysis of corn starch by microwave heating. In this particular experiment, the starch concentration was varied to study the effect of starch concentration. Different length of heating time for microwave assisted hydrolysis of starch was used. As a result, the color intensity was observed highest at pH 8, in lower concentration of starch, 0.7 g/ml and 10 minutes of microwave heating. Hence, it is concluded that alkaline condition is a suitable reaction medium to produce caramel color while the required time for caramelization completion is 1.5 hours.